An Analysis of In-House Training as a Managerial Strategy to Develop Professional Learning Communities in Primary Education - Haeriah, Yayah; Yusuf, Heri; Nur, Lutfi (Papanda Publisher, 2025)
Improving the quality of education in primary schools requires continuous teacher professional development, of which the Learning Community program is believed to be effective. However, the effectiveness of Learning Communities is strongly influenced by managerial strategies, including integrating In-house Training (IHT). This study analyzes the importance of IHT managerial strategies in supporting the effectiveness and sustainability of Learning Community programs in primary schools. This research uses a qualitative method with a literature study research type. A descriptive-analytical approach was applied to analyze and synthesize information from various literature sources relevant to primary school managerial strategies, IHT, and Learning Community programs. The data collection technique was document review, and data analysis was conducted through content analysis and data synthesis. The results of the literature analysis show that IHT managerial strategies play an important role in building the foundation of Learning Communities, developing collaboration and facilitation skills, and introducing learning innovations. The effectiveness of IHT integration in Learning Communities depends on careful planning, strong school leadership, and a comprehensive managerial strategy. This literature review concludes that the IHT managerial strategy is crucial in empowering Learning Community programs in primary schools. Effective and well-integrated IHT implementation in Learning Communities, supported by strong management, has the potential to improve learning quality and teacher professionalism significantly.